Snapshot of proteomic changes in Aspergillus oryzae during various stages of fermentative processing of pea protein isolate - Prem Prakash Das; Caishuang Xu; Yuping Lu; Azita Khorsandi; Takuji Tanaka; Darren Korber; Michael Nickerson; Nandhakishore Rajagopalan (Food Chemistry: Molecular Sciences, 2023)
Pea (Pisum sativum) is one of the most abundant and sustainable alternate source of protein. Although pea proteins have good quantities of most of the essential amino acids, they have a limited supply of tryptophan, methionine and cysteine. Moreover, pea proteins have poor techno-functional properties compared to proteins from animal sources, limiting their use in certain food applications. Bioprocessing techniques like solid-state fermentation (SSF) and enzymatic processing have been explored to improve the nutrient profile and functionality of pea proteins. However, there is a lack of information about proteomic changes in the food matrix during fermentation of the pea substrate. In this research, samples during SSF of pea protein isolate with Aspergillus oryzae were used for shotgun mass spectrometry (LC-MS/MS) analysis to identify the underlying functional pathways which play direct or indirect roles in enabling the colonization of the substrate leading to potential improvement of functional and nutritional value of pea protein. Results revealed the identity of A. oryzae proteins involved in different metabolic pathways that differed during various stages of SSF. Among them, methionine synthase was identified as an abundant protein, which catalyzes methionine biosynthesis. This might suggest how fermentation processes could be used to improve the presence of sulfur containing amino acids to rebalance the essential amino acid profile and improve the nutritional quality of pea proteins.